2019
DOI: 10.4236/aim.2019.96031
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Profiles of Selected Gram-Negative Bacteria Recoverable from Sewage and Sludge from Juja and Kibera Informal Settlements of the Larger Nairobi Metropolis

Abstract: Africa has experienced rapid urban migration in the past two decades. New informal settlements continue to emerge and expand but the sanitation provision of facilities has not improved at the same pace and this poses a serious health concern to the public especially the urban poor. Open sewage systems and sludge-clogged drainage systems as well as soil contaminated with industrial and domestic wastes are possible sources of germs that probably cause clinical infections and epidemics. In this cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(23 reference statements)
0
3
2
Order By: Relevance
“…These findings agree with a study on contamination of street food in Burkina Faso that enteric organisms emerge from cross contamination. 15 A study conducted on antimicrobial profile in Juja and Kibera found cefotaxime, ceftazidime and ciprofloxacin recorded a greater than 30% of antimicrobial resistance 16 this result is much lower than the one reported in the current study that recorded 25% increase. A study conducted by Ref.…”
Section: Discussioncontrasting
confidence: 70%
“…These findings agree with a study on contamination of street food in Burkina Faso that enteric organisms emerge from cross contamination. 15 A study conducted on antimicrobial profile in Juja and Kibera found cefotaxime, ceftazidime and ciprofloxacin recorded a greater than 30% of antimicrobial resistance 16 this result is much lower than the one reported in the current study that recorded 25% increase. A study conducted by Ref.…”
Section: Discussioncontrasting
confidence: 70%
“…15 The same observation was recorded by. 16 A study conducted on antimicrobial profile in Juja and Kibera found cefotaxime, ceftazidime and ciprofloxacin recorded a greater than 30% of antimicrobial resistance 17 this result is much lower than the one reported in the current study that recorded 25% increase. A study conducted by 18 observed that this increase in resistance is due to use in antibiotics in the treatment of diseases associated with poor unhygienic conditions.…”
Section: Discussioncontrasting
confidence: 70%
“…Our recent study among Gram-negative isolates from sewage, sludge, and soil recovered near these vending points revealed high resistances towards ceftazidime (9 %), ceftriaxone (12 %), amoxicillin-clavulanic acid (16%), gentamicin (11%) and ciprofloxacin (8%) [39]. Taken together, these results could be an indication that the resistant strains may be emanating from the immediate surroundings to contaminate slum foods.…”
Section: Discussionmentioning
confidence: 83%
“…Poor sanitation and chronic water shortages have been identified as significant contributors to enteric infections in slums such as Kibera [ 38 ]. Similarly, our previous study reported a diverse range of MDR bacteria belonging to Salmonella spp , Shigella spp , E. coli, and Klebsiella spp from sewage, sludge, and soil in Kibera near these food vending points [ 39 ]. Therefore, there is an excellent possibility that most of the enteric isolates among these foods emanate from unhygienic surroundings.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation